Removal of naphtenic acid from petroleum crude oil utilizing 2-methylimidazole liquid with the aid of Ca/AI2O3 and Ce/AI2O3 catalyst / Amier Khairan Shaidi - Shaidi, Amier Khairan (Faculty Of Applied Sciences, 2017)
Naphthenic acid (NA) is a carboxylic acid derivative compound commonly found in the petroleum erode oil. The presence of these compounds contributes to the acidity of erode oils and is one of the major sources of corrosion in oil pipelines and distillation units in erode oil refineries. Removing NA compounds from erode oils is regarded as one of the most crucial processes in heavy oil upgrading. In order to overcome this problem, catalytic deacidification method had been developed and used to reduce the total acid number values in crude oil. In this study, erode oil from Petronas Penapisan Melaka were investigated. The parameters used in this study were different catalyst calcination temperatures, catalyst loading, concentration reagent, reaction times and reaction temperature. 2-methylimidazole and ethanol was used as acid removal agent and monometallic calcium and cerium doped with alumina as a catalyst. The results showed that with the catalyst, the reduction of original TAN that was 2.43 mg KOH/g can be reduced to lower than 1 mg KOH/g. Ca/Al2O3 with a calcination temperature of 900°C gave a better reduction than Ce/Al203 with a calcination temperature of 900°C with 83.54% of TAN reduction (2.43 to 0.4) for Ca/Al2O3 catalyst and 71.19% (2.43 to 0.7) for Ce/Al2O3 catalyst. The best catalyst underwent several characterization methods such as X-Ray Diffraction Spectroscopy (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetry Analysis (TGADTA) for its physicochemical properties. It can be concluded that catalytic deacidification method was efficient and effective in removing NA from the erode oil thus lowering the TAN value less than 1 mg KOH/g.